Ai Weiwei : works : Beijing 1993-2003. - Chin-Chin Yap; Merewether, Charles; Napack, Jonathan (Timezone 8., 2003)
This monograph spans the life and work of the Beijing-based conceptual artist, publisher and architect, Ai Weiwei. While the book's focus is on key works produced in Beijing 1993-2003, the texts and interviews provide a broader context, following the artist's and his art's development from Xinjiang where he spent the his formative years with his exiled-father, to New York where in self-exile he was exposed to New York's experimental art for 13 years, and then back to Beijing where he produced the important body of new works that are the focus of this book...
biog., tent. p. 146
Engels
boek
Keywords: Ai, Weiwei